2021
DOI: 10.3389/fimmu.2021.736479
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Relieves Airway Remodeling By Inhibiting Epithelial-Mesenchymal Transition Through Downregulating TGF-β1 and Smad3 Expression In Vitro and In Vivo

Abstract: Airway remodeling is associated with dysregulation of epithelial-mesenchymal transition (EMT) in patients with asthma. Sinomenine (Sin) is an effective, biologically active alkaloid that has been reported to suppress airway remodeling in mice with asthma. However, the molecular mechanisms behind this effect remain unclear. We aimed to explore the potential relationship between Sin and EMT in respiratory epithelial cells in vitro and in vivo. First, 16HBE cells were exposed to 100 μg/mL LPS and treated with 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…On the other side, SN-treated rats showed significantly increased HXP levels in their cured wound tissue, indicating higher collagen content that might be correlated with its higher wound closure percentages. Our results were following previous results, which showed SN efficacy in positive regulation of subepithelial collagen deposition, and other tissue proteins that helped in relieving Airway remodeling in mice with asthma [ 62 ]. Similar effects of SN on the positive regulation of hydroxyproline and collagen proteins have been found in a nanofiber study for wound healing [ 63 ].…”
Section: Discussionsupporting
confidence: 90%
“…On the other side, SN-treated rats showed significantly increased HXP levels in their cured wound tissue, indicating higher collagen content that might be correlated with its higher wound closure percentages. Our results were following previous results, which showed SN efficacy in positive regulation of subepithelial collagen deposition, and other tissue proteins that helped in relieving Airway remodeling in mice with asthma [ 62 ]. Similar effects of SN on the positive regulation of hydroxyproline and collagen proteins have been found in a nanofiber study for wound healing [ 63 ].…”
Section: Discussionsupporting
confidence: 90%
“…He et al reported that SIN (607.2 mM) impeded 16HBe cell migration and suppressed the expression of MMP-7/-9 and vimentin. Additionally, SIN (35 and 75 mg/kg) reduced serum levels of specific IgE and IL-4 in ovalbumin-induced asthmatic mice, mitigated airway remodeling, lessened subepithelial collagen deposition, and inhibited EMT by downregulating TGF-B1 and Smad3 [ 211 ]. J.L.…”
Section: Organs Protectionmentioning
confidence: 99%
“…SC-induced M2 macrophage exosomes carrying miR-30b-5p reduce airway epithelial cell pyroptosis via restricting IRF7, resulting in restraining asthma progression [ 138 ]. EMT can be triggered by the TGF-β1/Smad3 signaling pathway and can support airway remodeling in asthma [ 139 ]. miR-21-5p is highly expressed in lung tissues of mice with ovalbumin (OVA)-induced asthma.…”
Section: Exosomal Ncrnas Regulate Macrophage-linked Intercellular Com...mentioning
confidence: 99%